Avaliação da expressividade oral: análise segundo perspectiva do fonoaudiólogo brasileiro - Valle, Mila Cruz do (2016)
The term oral expressiveness is used to refer to the sound that leaves a subject’s mouth, travels through space and is realized in another subject’sears, causing the impression that takes place in the act of speech, and which cannot be reviewed or reemitted. There is a variety of instruments used to evaluate aspects referring to oral expressiveness by a speech-language therapist. Purpose: to investigate the concepts and procedures adopted in the evaluation of oral expressiveness by Brazilian speech-language therapists. Method: this exploratory research was conducted by carrying out a survey of material (articles, books, theses and dissertations) published on the website of the Brazilian Society of Speech-Language Pathology and Audiology between 2000 and 2012. The variables studied were: the year and type of publication, the evaluated aspects, the profiles of the evaluators and the professionals being evaluated, the type of instruments and the evaluation parameters used. From 1,730 publications that researched voice professionals, considering the pre-established criteria, 45 publications were analyzed in this study. The data were analyzed descriptively by means of absolute and relative frequencies, and the chi-squared test was used in order to determine the association between the themes. Results: Most of the 45 publications were Master’s thesis (51.1%), published in 2007 (22.2%); newscasters were the most evaluated professionals (31.1%), and the majority of the evaluators were voice specialists (33.3%). Most studies (62.2%) employed only a perceptual-auditory analysis (APA), 46.3% associated sound and sense, 33.3% presented comparison studies, and 42.2% assessed non-verbal aspects as well. Among those that employed APA, vocal quality was the most commonly approached aspect (56.1%), followed by frequency variation (53.7%). Among the 17 studies that carried out acoustic analyses, the most used were fundamental frequency and frequency variation (both at 76.7%). There was no statistically significant association between the type of evaluation and the professionals who were evaluated in the studies. Conclusion: the investigation of concepts and procedures adopted by Brazilian speech-language therapists when evaluating oral expressiveness found a tendency towards employing a perceptualauditory analysis with the help of instruments to record parameters. There is no consensus among the authors regarding concepts and procedures, and priority is given to sound markers when compared to sense markers